Improving Auditor Performance Through A Spirituality Workplace Based on Tri Hita Karana, Hardiness Personality and Role Stress - Dewi, Mertyani Sari; Ferayani, Made Dwi; Eka Kusuma, Gusti Putu (International Journal of Social Science and Business, 2020)
This research is motivated by the importance of auditor performance in determining the performance of quality public accounting firm (KAP). The ability of auditors in a professional manner in using audit techniques and procedures to improve audit quality has an effect on the resulting performance. The study was conducted to provide empirical evidence regarding efforts to improve auditor performance through Tri Hita Karana-based workplace spirituality, hardiness personality and role stress in Public Accounting Firms (KAP) throughout Bali Province. The population in this study were all KAP auditors in Bali Province who were listed in the Directory published by the Indonesian Institute of Certified Public Accountants (IAPI) in 2020. The sampling technique was purposive sampling with the criteria used by the sample, including the auditors working in KAP throughout Bali Province. is still actively operating and has a minimum of 1 year of service or audit experience. This research was tested using a variance based structural equation model (Structural Equation Modeling-SEM) or Component based SEM with the SmartPLS 3.0 analysis tool. The test results show empirical evidence that Tri Hita Karana-based workplace spirituality weakens the effect of role conflict on auditors' performance, but Tri Hita Karana-based workplace spirituality does not moderate the effect of role ambiguity and role overload on auditor performance, while hardinessÂ  personality cannot moderate the effect of role conflict on performance. auditors, but hardiness personality weakens role ambiguity and role overload on auditor performance.